Improvement of bovine tuberculosis diagnosis - M. O. Baratov (Ветеринария сегодня)
Detection of animals with non-specific reactions to tuberculin is one of the major problems in bovine tuberculosis (TB) diagnosis. There is a need to find and improve methods for detection of the sensitization causes. This paper presents the results of comparative studies of different ways to stabilize red blood cells in order to obtain diagnosticums for indirect hemagglutination (IHA) test. The article describes the stages of red blood cells stabilization and sensitization and demonstrates the diagnostic significance of Fili stabilization method using formaldehyde as a fixative. The highest antibody titers (1:3000 and 1:4000) were received in hyperimmune sera of rabbits immunized with Mycobacterium bovis using a homologous diagnosticum. Practical importance of the sensitins homologous to the infection is shown during testing of 1,911 serum samples collected from animals of different categories (diseased; healthy and reacting to tuberculin; healthy and not reacting to tuberculin) with IHA test using diagnosticums produced from Mycobacterium bovis and Mycobacterium fortuitum. Based on the positive results of the IHA test, TB was diagnosed in 87.5% of animals originating from an infected farm during post-mortem examination. The results of the IHA test agreed with those of the intradermal tuberculin test in 37.7% of cases. Diagnostic antibody titers were found in 206 TB infected animals with no reaction to the intradermal test. However, the post-mortem examination revealed TB changes in internal organs. The obtained data suggest a possibility to use the IHA test to detect TB infected animals with non-specific reactions to tuberculin.